Analisis Kontrastif Antara Majas Elipsis Bahasa Arab dan Bahasa Indonesia - Muhammad Hafidz (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2023)
Contrastive analysis helps in foreign language teaching because of several assumptions: the more significant the differences between the first and second languages, the more acute the learning difficulties. Comparative results of first and second languages are needed to predict difficulties in learning a foreign language. This research is a literature study, the researcher collects data and information from books or references that explain the Arabic ellipsis figure of speech (Ikfia>’) and the Indonesian ellipsis figure of speech using a descriptive analysis approach. The analysis used is Contrastive Analysis, with the following steps: descriptive, comparing similarities and differences between two languages, and predicting difficulties. The results of this research are: 1) In Ikfia>’ and ellipsis figures of speech, the speaker omits certain words or expressions, the meaning of the omitted words is interpreted by the reader himself according to logic, 2) The researcher did not find any differences between the two. 3) Ikfia>’and ellipsis are included in the Level 0-Transfer difficulty category: meaning, there is no difference between the two. Students can transfer positively from the first language to the second language. ?They can speak in the Ikfia>’ style, just like they ?speak with ellipsis figures of speech in Indonesian.